PEMBINAAN KELOMPOK TANI MENJADI PETANI PENANGKAR BENIH UNGGUL SEBAGAI UPAYA DALAM MENGATASI KELANGKAAN BENIH PADI DI KECAMATAN BENGO KABUPATEN BONE - BDR, Muh. Farid; Nasaruddin, .; Ridwan, Ifayanti; Jamil, Hatta; Iswoyo, Hari; Mantja, Katriani; Nurfaida, . (Departemen Budidaya Pertanian Fakultas Pertanian UNHAS, 2020)
Problems faced by the Pangisoreng UPB partners and Allapporeng II farmer groups are the unavailability of superior seeds and scarcity of fertilizer during the planting season, low farming capital, the land is saturated with inorganic fertilizers and there is no use of organic fertilizers, resulting in soil cracking in the dry season and cause rice drought. The use of liquid fertilizer has not been carried out, the waste planting system is wasteful use of seeds, rat pest attacks due to the wrong planting system, and the knowledge and expertise of farmers in producing seeds, compost, liquid fertilizer / biopesticides are lacking; thus causing rice productivity and low farmer income. From the range of solutions offered, the activities that have been carried out are: (a) fostering farmer groups to become seed breeders so they can produce superior seeds independently, while encouraging new potential entrepreneurs, (b) training farmers to process locally available organic waste into fertilizer compost, liquid fertilizer / biopesticide, (c) improve the planting system from hambur into a planting system, move through seed demonstration plot and (d) provide assistance during the activity. The output targets to be achieved on PKM are: Superior seed production, compost production, liquid fertilizer / biopesticide, increased productivity from 5.5 tons / ha to 8-9 tons / ha. From the implementation of the activities carried out it can be concluded that the activities were welcomed by members of partner farmer groups because they were classified as new. Making compost and liquid organic fertilizer can be done by utilizing local materials and considering the function of each ingredient.Keywords: Rice seeding, compost, liquid fertilizer, planting system. ABSTRAKPermasalahan yang dihadapi oleh mitra UPB Pangisoreng dan kelompok tani Allapporeng II adalah tidak tersedianya benih unggul dan kelangkaan pupuk saat musim tanam, modal usaha tani yang rendah, lahan sudah jenuh dengan pupuk anorganik dan tidak ada penggunaan pupuk organik, sehingga terjadi keretakan tanah pada musim kemarau dan menyebabkan padi kekeringan. Penggunaan pupuk cair belum dilaksanakan, sistem tanam hambur yang boros penggunaan benih, serangan hama tikus akibat sistem tanam yang salah, serta pengetahuan dan ketermpilan petani dalam memproduksi benih, pupuk kompos, pupuk cair/biopestisida yang kurang; sehingga menyebabkan produktivitas padi dan pendapatan petani rendah. Dari rangkaian solusi yang ditawarkan, kegiatan yang telah dilaksanakan adalah: (a) pembinaan kelompok tani menjadi penangkar benih sehingga mampu memproduksi benih unggul secara mandiri, sekaligus mendorong menjadi calon wirausaha baru, (b) melatih petani mengolah limbah organik yang tersedia secara lokal menjadi pupuk kompos, pupuk cair/ biopestisida, (c) memperbaiki sistem tanam dari hambur menjadi sistem tanam pindah melalui demplot perbenihan serta (d) melakukan pendampingan selama kegiatan berlangsung. Target luaran yang ingin dicapai pada PKM adalah: Produksi benih unggul, produksi kompos, pupuk cair /biopestisida, peningkatan produktivitas dari 5,5 ton/ha menjadi 8-9 ton/ha. Dari pelaksanaan kegiatan yang dilakukan dapat disimpulkan bahwa kegiatan disambut baik oleh anggota kelompok tani mitra karena tergolong baru. Pembuatan kompos dan pupuk organik cair dapat dilakukan dengan memanfaatkan bahan local dan mempertimbangkan fungsi dari masing-masing bahan.Kata kunci: Perbenihan padi, kompos, pupuk cair, sistem tanam